Efektivitas Model Pembelajaran Contextual Teaching and Learning Pada Mata Pelajaran Fiqih di MTs Negeri Binjai - Regita, Selvi; Ginting, Nurman (Yayasan Rahmat Islamiyah, 2024)
This research aims to evaluate how effective the use of the Contextual Teaching and Learning (CTL) learning model is in Fiqh subjects. The method used in this research is the descriptive qualitative method. Data collection techniques use obeservation and interviews. The research subjects were Fiqh subjects teacher and Binjai State MTs students. The results of the research show that the application of the Contextual Teaching and Learning (CTL) learning model in Fiqh subjects implemented at MTs Negeri Binjai is quite effective as students are able to understand the subject matter by interpreting the meaning of the material using their own language, applying and practicing it in everyday life.